PERANAN GURU AKIDAH AKHLAK DALAM MENANAMKAN NILAI-NILAI KARAKTER SISWA KELAS X MA TARBIYAH WALADIYAH PULAU BANYAK - Lily Aulia (Jurnal Iqtirahaat, 2024)
The aim of the research is to determine the role of moral aqidah teachers in instilling character values ​​in class X MA Tarbiyah Waladiyah Pulau Banyak students. The type of research is qualitative research. The subjects or informants in the research were madrasa heads, teachers and students using purposive sampling techniques. Data collection methods include observation, interviews and documentation. Miles and Huberman model data analysis according to this theory, qualitative data analysis can be carried out using a flow and interactive model, namely through the stages of the data collection process, data reduction, data presentation and conclusion presentation. The results of the research are that moral belief teachers have a very important role in instilling character values ​​in students at school. The role of the teacher is as a role model for students, the teacher is a figure who is used as an example in attitude and behavior. Teachers also provide motivation or good advice to their students, especially moral belief teachers who play an important role in this matter.